مقامات جلال الدين السيوطي: دراسة نقدية ............................................... Maqamat by Jalal ul-Din al-Suyuti: A Critical Study - عقيب, إسماعيل عمارة (الدراسات الإسلامية, 2018)
The writer of this paper highlights the literary genius of Jalāl ul-Dīn al-Suyuti the famous Egyptian scholar of ninth century hijrah. This he has done by introducing al-Suyuti’s work in the Arabic literary genre known as Maqamat. He introduces this genre with reference to its founders Badi al-Zaman al-Hamadhani and Qasim b. Ali al-Ḥariri and shows the distincetive traits of style and content introduced in this literary field by al-Suyuti. According to the writer, the extensive and profound scholarship of al- Suyuti is fully reflected in his Maqamat apart from his exceptional literary skills. In the beginning of this paper, the writer has provided biographical details about al-Suyuti, his rich academic development and varied contribution to Islamic scholarship.